Images and Ideals: Counselling Women and Girls in a "Thin-is-in" Culture - Saraceni, Reana; Russell-Mayhew, Shelly (Canadian Journal of Counselling and Psychotherapy, 2008)
Two well-cited studies (Garner, Garfinkel, Schwartz & Thompson, 1980; Wiseman, Gray, Mosimann, & Ahrens, 1992) examined the changing body shape of Playboy centrefolds from 1959 to 1988 and noted that their body weights were significantly lower than those ofthe average female. The current study updates and examines changes in body measurements and weight across four decades using a multivariate one-way Analysis of Variance. Chisquareanalysis of the models’ expected weight and actual body mass index (BMI) indicates that the female body weight standard has become increasingly restrictive. Implications for counselling girls and women are discussed within the feminist therapeutic context.